A FRAMEWORK FOR TRANSDISCIPLINARY RADIOCARBON RESEARCH: USE OF NATURAL-LEVEL AND ELEVATED-LEVEL 14C IN ANTARCTIC FIELD RESEARCH. Issue 5 (31st October 2021) - Venturelli, Ryan A; Vick-Majors, Trista J; Collins, Billy; Gagnon, Alan; Kasic, Kathy; Kurz, Mark D; Li, Wei; Priscu, John; Roberts, Mark; Rosenheim, Brad E
ABSTRACT: Radiocarbon ( 14 C) is an isotopic tracer used to address a wide range of scientific research questions. However, contamination by elevated levels of 14 C is deleterious to natural-level laboratory workspaces and accelerator mass spectrometer facilities designed to precisely measure small amounts of 14 C. The risk of contaminating materials and facilities intended for natural-level 14 C with elevated-level 14 C-labeled materials has dictated near complete separation of research groups practicing profoundly different measurements. Such separation can hinder transdisciplinary research initiatives, especially in remote and isolated field locations where both natural-level and elevated-level radiocarbon applications may be useful. This paper outlines the successful collaboration between researchers making natural-level 14 C measurements and researchers using 14 C-labeled materials during a subglacial drilling project in West Antarctica (SALSA 2018–2019). Our strict operating protocol allowed us to successfully carry out 14 C labeling experiments within close quarters at our remote field camp without contaminating samples of sediment and water intended for natural level 14 C measurements. Here we present our collaborative protocol for maintaining natural level 14 C cleanliness as a framework for future transdisciplinary radiocarbon collaborations.